Sodium ascorbate kills Candida albicans in vitro via iron-catalyzed Fenton reaction: Importance of oxygenation and metabolism - Avci, Pinar; Freire, Fernanda [UNESP]; Banvolgyi, Andras; Mylonakis, Eleftherios; Wikonkal, Norbert M.; Hamblin, Michael R. (Taylor & Francis, 2016)
Aim: Ascorbate can inhibit growth and even decrease viability of various microbial species including Candida albicans. However the optimum conditions and the mechanism of action are unclear. Materials/methodology: Candida albicans shaken for 90 min in a buffered solution of ascorbate (90 mM) gave a 5-log reduction of cell viability, while there was no killing without shaking, in growth media with different carbon sources or at 4°C. Killing was inhibited by the iron chelator 2,2′-bipyridyl. Hydroxyphenyl fluorescein probe showed the intracellular generation of hydroxyl radicals. Results/conclusion: Ascorbate-mediated killing of C. albicans depends on oxygenation and metabolism, involves iron-catalyzed generation of hydroxyl radicals via Fenton reaction and depletion of intracellular NADH. Ascorbate could serve as a component of a topical antifungal therapy.
Keywords: ascorbate; Candida albicans; hydroxyl radicals; oxidative stress; vitamin C